Critiquing the Use of the Term Restorative Justice in Narcotics Cases - Susilo, Erwin; Setiawan Negara, Dharma (Jurnal Ius Constituendum, 2025)
This study aims to evaluate the appropriateness of using the term “Restorative Justice” (RJ) in the settlement of narcotics cases at the investigation and inquiry stages in Indonesia, as regulated under the Regulation of the Chief of the Indonesian National Police Number 8 of 2021 concerning the Handling of Criminal Offenses Based on Restorative Justice (INPR 8/2021). The background of this research arises from the conceptual tension between RJ’s core principles—namely, victim-offender dialogue and community involvement—and the actual practice in narcotics cases, where the offender is simultaneously the victim and no external harmed party is present. The urgency of this writing lies in the widespread use of RJ terminology in policy documents without adequate alignment to its philosophical foundations, which may create confusion in legal interpretation and practice. Using normative juridical methods, this research employs conceptual and statutory approaches to find that the substance of INPR 8/2021 is more aligned with Rehabilitation Theory (RT), particularly the medical model, which views the offender as a patient in need of treatment rather than as a morally responsible agent. This study provides a novel conceptual clarification by framing INPR 8/2021 within the medical model of rehabilitation rather than traditional RJ. This reinterpretation contributes to more accurate legal discourse and supports the development of coherent and normatively sound drug policy frameworks in Indonesia, ensuring that the use of legal terminology reflects the actual purpose and design of the policy.